Sistem Informasi Pelaporan Kesehatan Ibu dan Anak Berbasis Web dengan Pendekatan Agile Scrum - Rika Oktariani (PT. Alesha Media Digital, 2025)
Maternal and Child Health (Kesehatan Ibu dan Anak/KIA) service records at primary health centers in Indonesia remain largely paper-based, causing monthly LB3 KIA reporting to take up to six hours and exposing the workflow to duplicate entry. This study designs and implements a web-based KIA reporting information system at Puskesmas Alang-Alang Lebar Palembang using the Agile Scrum approach, executed across four two-week sprints with midwives and posyandu cadres acting as functional product owners. Data were collected through two weeks of service workflow observation, interviews with five key informants totaling 195 minutes, and analysis of nine standard KIA clinical documents. The system was developed using PHP 8.1, the Laravel 10 framework, and MySQL 8 database, producing 35 controllers, 7 models, and 52 views in 4,520 lines of code. Black-Box testing of 35 scenarios achieved 100% functional conformance, while User Acceptance Testing with 14 respondents recorded a 92% acceptance score. The recapitulation time for LB3 KIA reports was reduced from six hours to 4.5 seconds. The study contributes an integrated database model spanning eight KIA modules and empirical validation of Agile Scrum for primary healthcare information systems serving users with heterogeneous digital literacy.